Strategic Analysis Of The Acquisition Of Pt. Axis Telekom Indonesia By Pt. Xl Axiata - Prasetyaningsih, Insiwijati; Marlitta Stefia, Cheryl (Riviera Publishing, 2022)
Introduction: XL began out its enterprise as a wellknown buying and selling and offerings enterprise on 6 October 1989 beneathneath the call PT Grahametropolitan Lestari. In 1996, XL input the telecommunications quarter after acquiring a GSM 900 running license and formally released GSM offerings. Method: To achieve this goal, research was carried out with using pure quantitative research and then to process the data used descriptive quantitative research. Secondary data sources in this study from the internet or research from another author. Then secondary data is also obtained from previous articles. Secondary data sources from this research are documents from articles, and journals about merger. Results: On December 26, 2013, XL signed an settlement to collect AXIS. Conditional income buy settlement (CSPA) carried out with Saudi Telecom Company (STC) and Teleglobal Investment BV (Teleglobal), that's a subsidiary of STC. XL is stated to be paying the cost the agreed nominal proportion and could pay a part of the debt and obligations AXIS. Conclusion: There is a significant effect of acquisition on the stock market value PT. XL axiata tbk. at three years (12 Quarterly) after the acquisition. XL stock market value axiata tbk. experienced a decrease in the average value, from 44,860,462,622,714.59 to 37,496,902,892,475.75..